Antioxidant and antimicrobial properties of Pandanus conoideus Lam / Intan Masyitah Rumli - Rumli, Intan Masyitah (2008)
An antioxidant is defined as a substance that can delay and destroy excess free radicals and repair oxidative damage in biomolecules. The antioxidants are believed to play a very important role in the body defence system against reactive oxygen species (ROS), which are the harmful by products generated during normal cell aerobic respiration. Increasing intake of dietary antioxidants may help to maintain an adequate antioxidant status and, therefore, the normal physiological function of a living system. Our study of interest is to investigate the antimicrobial and antioxidant properties of P. conoideus extract by using different assays. P. conoideus found to be one of the potential natural antioxidant and sources and able to boost up the body immune system. The determination of antioxidant properties were carried out by using four different assays, specifically total phenolic compound, DPPH radical scavenging assay, xanthine/xanthine oxidase superoxide scavenging assay, and tyrosinase inhibitory assay while the antimicrobial properties of this extract was determined by using the micro broth dilution method. The P.conoideus extract was found to have antioxidant properties but no positive result shown for the antimicrobial screening of the extract. It was observed that the highest antioxidant capacity of the extract was shown when xanthine/xanthine oxidase superoxide scavenging assay was used relative to the other three methods.